Mode-Locked Thulium Ytterbium Co-Doped Fiber Laser with Graphene Oxide Paper Saturable Absorber. (14th January 2015) - Azooz, S. M.; Harun, S. W.; Ahmad, H.; Halder, A.; Paul, M. C.; Pal, M.; Bhadra, S. K.
Abstract: A mode-locked thulium ytterbium co-doped fiber laser (TYDFL) is proposed and demonstrated by using a commercial graphene oxide (GO) paper as saturable absorber (SA). The GO paper is sandwiched between two fiber ferrules and incorporates a ring laser cavity to generate soliton pulse train operating at 1942.0nm at a threshold multimode pump power as low as 1.8 W. The mode-locked TYDFL has a repetition rate of 22.32 MHz and the calculated pulse width of 1.1 ns. Even though the SA has a low damage threshold, the easy fabrication of GO paper should promote its potential application in ultrafast photonics.